P660 Extra-genital ciprofloxacin-resistant neisseria gonorrhoeae infections among sexual-health clinic users in lima, peru. (14th July 2019) - Vargas, Silver; Qquellon, Luz; Durand, David; Allan-Blitz, Lao-Tzu; Konda, Kelika; Caceres, Carlos; Klausner, Jeffrey
Abstract : Background: The increasing prevalence of drug-resistant Neisseria gonorrhoeae (NG) infections has caused great concern. NG susceptibility to ciprofloxacin can be reliably predicted using a real-time polymerase chain reaction (PCR) assay for the determination of mutation at codon 91 of the gyrase A ( gyr A) gene. Ciprofloxacin remains the empiric antimicrobial recommended to treat NG infections in Peru, however local data are limited regarding the prevalence of ciprofloxacin resistance. Methods: Clinical swab specimens from pharyngeal and rectal anatomic locations were collected quarterly between 2013 and 2016 from a cohort of men who have sex with men (MSM) and transgender women in Lima, Peru. NG detection was done using Aptima Combo 2 assay (Hologic Inc, USA). NG-Positive samples were selected for DNA extraction using High Pure PCR Template Preparation Kit (Roche Inc, USA). DNA was amplified using a probe-based Real-time PCR assay to determine point mutations at codon 91 of the gyr A gene. Results: Overall, 156 individuals had at least one sample that tested positive for NG by the Aptima assay, 61 (39%) of whom reported a previous sexually transmitted infection diagnosis and 50 (32%) were HIV-infected. Of the 80 participants with gyr A genotype results available, 67 (84%) had at least one sample with a gyr A mutant NG strain; also, 5 individuals alternated between wild type and mutant NG strain infections during follow up in the same anatomical site. Conclusion: We report the prevalence of individuals with extragenital NG infections with a gyr A mutation conferring ciprofloxacin resistance. While most countries of the region recommend ceftriaxone for NG treatment, Peruvian guidelines need to be updated urgently given the high frequency of ciprofloxacin resistance. The use of molecular genetic markers may facilitate surveillance for antimicrobial resistance. Disclosure: No significant relationships.